Sistem Pendukung Keputusan Pemilihan Server Hosting Dan Domain Terbaik Untuk WEB Server Menerapkan Metode VIKOR - M. Iqbal Kurniansyah; Sinar Sinurat (STMIK Budi Darma, 2020)
Hosting is a place or internet service to make the website pages that you have created online and can be accessed by other people. Meanwhile, Hosting itself is an internet service that provides server resources for rent, allowing organizations or individuals to place information on the internet in the form of HTTP, FTP, EMAIL or DNS. Domain is an identifier string that is used to identify a server such as a web server or mail server on a computer network or the internet for easy access by the user. By using a domain you no longer need to remember the IP address of the server you are going to, because everything has been regulated by the Domain Name Server (DNS) so that the domain you write about will be directly connected to the IP address of the server. WebServer is a software that provides data-based services and functions to receive requests from HTTP or HTTPS on a known client and usually known as a web browser (Mozilla Firefox, Google Chrome) and to send back the results in the form of several web pages and in general. will be in the form of an HTML document.